2019
DOI: 10.1111/ecc.13126
|View full text |Cite
|
Sign up to set email alerts
|

A sense of understanding and belonging when life is at stake—Operable lung cancer patients' lived experiences of participation in exercise

Abstract: Objective To explore the lived experiences and social benefits among patients with operable Non‐small‐cell lung cancer who participated in an exercise intervention. Methods Eighteen patients enrolled in an exercise intervention at 2 weeks post‐surgery participated in qualitative interviews at three time points. A phenomenological hermeneutical approach comprised the epistemological stance inspired by Ricoeur's philosophy. Analysis and interpretation provided descriptions that captured the meaning of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Exercises and meetings with people who had had the same experiences were very important for them, as they made it easier to tolerate the illness and therapy, as well as creating an atmosphere of respect and minimalised fear. 44 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercises and meetings with people who had had the same experiences were very important for them, as they made it easier to tolerate the illness and therapy, as well as creating an atmosphere of respect and minimalised fear. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Thanks to such procedures, patients feel cared for, have a sense of belonging to a community, are motivated to exercise, can freely communicate with people in a similar situation and benefit from interpersonal contacts and quick access to reliable advice and news in case of doubt, without waiting in a queue to see the doctor. 44 , 46 Sui et al conducted a study where patients who had undergone surgical NSCLC resection used the We-Chat app-based education and rehabilitation program (WERP) for 12 months, and found that the application significantly improved patients’ QoL and well-being. The phone application WERP is based on disease-related health education, rehabilitation exercise guidance, daily activity supervision and psychological support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By sharing their own story of illness and listening to others' stories, the participants became equipped with a language of what they had lived through in the vulnerable period of illness. Other studies have demonstrated how peer support and sharing experiences of illness have a significant impact on the individual's illness transition experiences and orientation into a new life situation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…If we look at human history, we can see that being part of a social community is something that has created far better conditions for a healthy life and that it stands in contrast to an egocentric project, where the only important thing is to optimize physical fitness. In this regard, Missel, Borregaard, Schoenau, and Sommer (2019) have pointed out that precisely a sense of community and understanding can be established for patients who participate in exercise, with exercise facilitating community and increasing social capital.…”
Section: Discussionmentioning
confidence: 99%